The Reflection of Local Wisdom of Farmer Community’s World View in Brebes Regency - Bivit Anggoro Prasetyo Nugroho; Muhamad Riyanton; Etin Pujihastuti; Dini Anggraheni; Melia Istiani (Program Studi Pendidikan Bahasa Inggris Fakultas ilmu Budaya, 2023)
The farmer community’s collective minds in Brebes Regency may be classified with linguistic expressions at the lingual unit level of word, phrase, sentence, and discourse. The farmer community's local wisdom may be identified through linguistic category and expression, covering local cultural, astronomical, technical, economic, and social wisdom. This qualitative research describes the local wisdom of the farmer community in Brebes Regency related to the Javanese language and culture through linguistic expression in agriculture, husbandry, and fishery. The analysis model used an ethnoscience model called The New Ethnography. The local wisdom refers to the farmer community's significant local wisdom, which is the farmer community's choice to remain becoming farmer. The research shows that the farmer community's view of life is their way to view this life, that humans are created as individuals and social beings. The farmer community's mindset may be observed from their daily behaviors of simplicity, hard work, and maintaining harmony between nature and humans. Keywords: local wisdom, view of life, farmer